The Impact of Drainage on the Performance of Low Volume Sealed Roads - Andrew Otto (Sustainability, 2020)
Under the Research for Community Access Partnership (ReCAP) funded by the United Kingdom Aid (UKaid) program, a project entitled ‘Development of Specifications for Low Volume Sealed Roads through Back Analysis’ was carried out. Previous studies on the performance of low volume sealed roads have emphasized the importance of good drainage to ensure good performance. The emphasis has been on providing sealed shoulders, adequate crown height, and adequate camber. These studies have not related these cross-sectional features with materials characteristics. This paper investigates the influence of each of these features on the performance of low volume sealed roads and their relation to pavement materials. The features were considered each one at time, using a matrix of three levels of the value of each feature and three levels of performance categories. Thus, presenting a 3 × 3 performance matrix for each factor. Assessment of the matrices showed that provision of sealed shoulders permits the use of materials of higher plasticity (PI ≤ 16 and PM ≤ 560) without compromising performance compared to that permissible for sections with unsealed shoulders (PI ≤ 10 and PM ≤ 240). These results can be used to supplement existing selection criteria for road base material of low volume roads.